2002
DOI: 10.1021/ja0164069
|View full text |Cite
|
Sign up to set email alerts
|

Weak, Improper, C−O···H−C Hydrogen Bonds in the Dimethyl Ether Dimer

Abstract: The ground-state rotational spectrum of the dimethyl ether dimer, (DME)(2), has been studied by molecular beam Fourier transform microwave and free jet millimeter wave absorption spectroscopies. The molecular beam Fourier transform microwave spectra of the (DME-d(6))(2), (DME-(13)C)(2), (DME-d(6))...(DME), (DME-(13)C)...(DME), and (DME)...(DME-(13)C) isotopomers have also been assigned. The rotational parameters have been interpreted in terms of a C(s) geometry with the two monomers bound by three weak C-H...O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 17 publications
10
79
0
1
Order By: Relevance
“…The O···H and F···H distances are in line with those observed for the complexes oxirane-TFM, [6] oxirane-difluoromethane [7] and dimethyl ether dimers, [5] once the different nature of C=O···H and C-O···H hydrogen bonds is taken into account. Actually, the F···H distance is slightly longer than that of other complexes (about 0.1 ).…”
Section: Conformation and Structuresupporting
confidence: 85%
See 2 more Smart Citations
“…The O···H and F···H distances are in line with those observed for the complexes oxirane-TFM, [6] oxirane-difluoromethane [7] and dimethyl ether dimers, [5] once the different nature of C=O···H and C-O···H hydrogen bonds is taken into account. Actually, the F···H distance is slightly longer than that of other complexes (about 0.1 ).…”
Section: Conformation and Structuresupporting
confidence: 85%
“…[4,[6][7][8] The deviation from linearity of the C-H···O and C-H···F angles is considerable (51 and 668, respectively), as seen in previous cases. [5][6][7] This reveals the weak hydrogen bond nature of both types of competing interactions. The C-H···O bond is bent by presence of the C-H···F interactions and vice versa.…”
Section: Conformation and Structurementioning
confidence: 90%
See 1 more Smart Citation
“…It has been shown that the OÀH···Cl hydrogen bond is slightly preferred to the O À H···F one, [8] but their energies have been estimated to be rather small (4-5 kJ mol À1 ). [8] These energy values are similar to those estimated for weak C À H···O, [9] C À H···F [10] or CÀH···p [11] interactions, which are classified as weak [12] or blue-shifted hydrogen bonds. [1] The simplest molecules containing halogen atoms (F 2 and ClF) react with water.…”
supporting
confidence: 70%
“…The relevance of the effect can be discussed quantitatively: Taking Kr as the study case for comparison of theory and experiment, we see that the binding energy (Figure 3) is about 1 kJ mol À1 higher than e = 1.65 kJ mol À1 , which can be compared with the expected value of 1.37 kJ mol À1 for pure vdW interactions (Table 1). The magnitude of the binding energy for Kr and Xe is therefore in the range of the so-called weak hydrogen bonds [21,22] (strong hydrogen bonds can be up to an order of magnitude stronger), and it is important to stress that only a fraction (ca. 50 % for Kr) is accounted for by vdW forces.…”
Section: Methodsmentioning
confidence: 99%